PENDAMPINGAN PEMBELAJARAN MODEL BLENDED LEARNING BAGI GURU MADRASAH PINGGIRAN DALAM MENGHADAPI ERA 5.0 - Ahmad Royani; Asmi Faiqatul Himmah; Muhammad Junaidi (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
The development of information technology has given strategic role for supporting teaching and learning in progress. It is able to be conducted by the phenomena of covid 19 happened. Model of teaching and learning has transformed in many activities such as online (daring) and offline (luring). This devotion is focused on Madrasah which is located in isolated area at Kalibaru subdistrict of Banyuwangi east Java in 2021. This devotion concentrates to the teaching and learning based on blended learning in Practice for welcoming 5.0 era. ABCD approach is used to find out the strength of Madrasah. From the activities done in the devotion are able to be concluded that blended learning is one of model which should be Mastered and implemented in teaching and learning process. Training of trainer in giving deeper understanding about the way to implement blended learning, aims to give new strategy through media for teachers in madrasah using gadget as mobile phone wisely. For further then, the usage of internet media can be optimized to support teaching and learning in progress.